Study of charge transport in blends of natural rubber and poly(o-methoxyaniline) based on a resistor network statistical model - Nagashima, Haroldo Naoyuki [UNESP]; Cardoso, L. S. [UNESP]; Malmonge, J. A. [UNESP] (Elsevier B.V. Sa, 2009)
A statistical model of a resistor network is proposed to describe the electrical properties, real and imaginary components of ac conductivity, of natural rubber (NR) and poly(o-methoxyaniline) (POMA) blend. It takes into account the polydispersivity of the material as well as intrachain and interchain charge transport processes in the POMA phase and the interfacial processes between conducting islands and the insulating matrix. The model calculates the alternated conductivity of these structures by transfer matrix technique. The conductance between two neighboring sites of the natural rubber was determined by Dyre's Equation. The conductance between sites of the conductive polymer, using the resonance quantum-tunnelling model, is obtained by the equation generalized of Breit-Wigner. The interface conductance between both polymers was determined by means of the combination of these two equations assuming the resistances of them are linked in series. The model reproduced the measured conductivity in NR/POMA films in a large range of frequencies. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Statistical model; Resistor network; Alternating conductivity; Resonance quantum tunnelling; Natural rubber